Environmental and Green Orientation as Drivers of Firm Performance: A Natural Resource-Based View Review - Suroto Suroto (Politeknik Siber Cerdika Internasional, 2026)
Background: Sustainable development has moved environmental practices from compliance to strategic economic resources. Based on the Natural Resource-Based View (NRBV), this paper conducts a systematic review of the impact of green and environmental orientation upon competitive strategy and firm performance. Objective: This study aims to (1) identify dominant research themes in the green and environmental orientation literature, (2) examine prevailing theoretical and methodological approaches, and (3) develop an integrative NRBV-based strategic framework explaining how sustainability-oriented resources are converted into competitive strategy and superior firm performance. Methods: Following the PRISMA 2020 guidelines, a systematic search of the Scopus database was conducted in January 2025 using terms including